Horizontal, Vertical, and Conglomerate FDI: Evidence from Cross Border Acquisitions - Nils Herger; Steve McCorriston (Swiss National Bank, Study Center Gerzensee, 2014)
By using data on cross-border acquisitions (CBAs), this paper explores the distribution of the strategies pursued when multinational enterprizes integrate a foreign subsidiary into their organisational structure. Based on a measure of vertical relatedness, each of the 165,000 acquisitions in our sample covering 31 source and 58 host countries can be classified as horizontal, vertical, or conglomerate. Three novel features of CBAs are highlighted. First, horizontal and vertical CBAs are relatively stable over time. Second, substantial parts of CBAs involve conglomerate acquisitions. Third, the wave-like growth of CBAs arises primarily from changes in conglomerate activity, which responds to international valuation differences between financial markets.
Keywords: F15; F21; F23; F33; 330; Cross-Border Acquisitions; Multinational Firm; Horizontal Merger; Vertical Merger; Conglomerate Merger